PUBLIC ADMINISTRATION TOOL DEVELOPMENT: PROBLEMS, PROSPECTS - G. G. Kouznetsova (Модернизация, инновация, развитие)
The need to transform the present Russian economics public administration mechanism relates to changes in the public administration’s object and subject as well as with the aims and tasks of rendering public services. Main principles of the new approach to the use of public administrationinstruments are trust, approach to information, openness, responsibility, result, account for budget possibilities and consistency.